Haymaking and utilization - Adie, Aberra; Getahun, Elizabeth; Bezabih, Melkamu; Worku, Tigist (International Livestock Research Institute, 2024)
Farmers around North Shewa Zone, Ethiopia, have good knowledge and experience of hay making. They make hay mainly from naturally growing pasture during the main rainy season (July–September). Harvesting and hay making are normally done in October.